kidd (1973)
kid n [One type of slingshot] is made of an alder stalk, with rubber attached to the stalk and the "kidd". The "kidd" is usually made of leather, preferably the tongue of an old boot. DNE-cit JH 10/73 Used I Used I 1 Used I [see 'rubber-gun]; kid-board, kid's eye Checked by Raji Sreeni on Mon 06 Jul 2015